2013
DOI: 10.1103/physreva.88.043821
|View full text |Cite
|
Sign up to set email alerts
|

Correlation measurements with on-off detectors

Abstract: We present a general method to detect nonclassical radiation fields with systems of on-off detectors. We especially study higher order correlations for the identification of nonclassical radiation. This allows us to directly characterize quantum correlations by the statistics measured with systems of on-off detectors. Additionally, we generalize our method to multiple detector systems for measurements of correlations between light fields. We also consider multi-mode radiation fields and isolate nonclassicality… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(92 citation statements)
references
References 42 publications
1
91
0
Order By: Relevance
“…Recently, alternative hierarchies of kth-order nonclassicality witnesses have been formulated, based on the 'click' statistics of on-off detectors [16][17][18]. Compared to the conditions on the 'click' statistics, an advantage of conditions (3) is that they are formulated in terms of normalized CFs, which are invariant to optical losses or detection inefficiency [13].…”
Section: Witnessing Nonclassicalitymentioning
confidence: 99%
“…Recently, alternative hierarchies of kth-order nonclassicality witnesses have been formulated, based on the 'click' statistics of on-off detectors [16][17][18]. Compared to the conditions on the 'click' statistics, an advantage of conditions (3) is that they are formulated in terms of normalized CFs, which are invariant to optical losses or detection inefficiency [13].…”
Section: Witnessing Nonclassicalitymentioning
confidence: 99%
“…1. It is worth mentioning that in this form P N is proportional to the generating function of the click statistics, which has been used to formulate nonclassicality criteria [21]. Denoting by P α ðβÞ the P representation (1) of the displaced state ρ α , the click-counting phase-space function can be written as …”
mentioning
confidence: 99%
“…In previous works, we have shown that the binomial form requires a reformulation of nonclassicality conditions [24,28]. Moments of the click counting statistics can be used to identify quantum correlations -even between multiple detector systems.…”
Section: Heralded State Preparation With Click Detector Systemsmentioning
confidence: 99%
“…Fourth, additional features may appear when generalized detection processes are involved, e.g., two-photon absorption within the diodes, cf. [28]. Similarly, arbitrary noise models may be included at any stage of the protocol description.…”
Section: Fig 7: (Color Online)mentioning
confidence: 99%
See 1 more Smart Citation